The relationship between blood potassium, blood lactate, and electromyography signals related to fatigue in a progressive cycling exercise test - Tenan, M. S.; McMurray, R. G.; Blackburn, B. T.; McGrath, M.; Leppert, K. (Journal of Electromyography and Kinesiology, 2011)
Local muscle fatigue may be related to potassium efflux from the muscle cell and/or lactate accumulation within the muscle. Local fatigue causes a decrease in median frequency (MPF) of the electromyogram`s power spectrum during isometric contractions but its relationship to changes in potassium and lactate during dynamic exercise is equivocal. Thus, this investigation evaluated relationships between changes in the MPF from the vastus lateralis and blood levels of lactate and potassium during an incremental cycling test and recovery. Trained cyclists (n = 8) completed a discontinuous, graded cycle test to exhaustion under normal and glycogen-reduced conditions. The glycogen reduced condition promoted an environment of lower lactate production while permitting a consistent potassium response. Blood samples and maximal isometric EMG data were collected at the end of each stage and during recovery. Maximal lactate levels were 60% lower in the glycogen reduced condition; potassium was similar between trials. MPF did not change significantly at volitional fatigue. Further, MPF was not significantly related to lactate (p > 0.27) or potassium (p > 0.16) in either condition. Though both lactate and potassium have been implicated as factors relating to local muscle fatigue, neither is significantly related to changes in MPF during or after progressive exercise on a cycle ergometer.